Genetic immunization for antibody generation in research animals by intravenous delivery of plasmid DNA. (February 2006) - Kay Bates, Mary; Zhang, Guofeng; Sebestyén, Magdolna G.; Neal, Zane C.; Wolff, Jon A.; Herweijer, Hans
Genetic immunization is an attractive approach to generate antibodies because native proteins are expressed in vivo with normal posttranscriptional modifications, avoiding time-consuming and costly antigen isolation or synthesis. Hydrodynamic tail or limb vein delivery of naked plasmid DNA expression vectors was used to induce antigen-specific antibodies in mice, rats, and rabbits. Both methods allowed the efficient generation of high-titer, antigen-specific antibodies with an overall success rate of Western detectable antibodies of 78% and 92%, respectively. High-titer antibodies were typically present after 3 hydrodynamic tail vein plasmid DNA deliveries, 5 weeks after the initial injection (i.e., prime). For hydrodynamic limb vein plasmid DNA delivery, two deliveries were sufficient to induce high-titer antibody levels. Tail vein delivery was less successful at generating antibodies directed against secreted proteins as compared with limb vein delivery. Material for screening was generated by transfection of the immunization vector into mammalian cell lines. The cell line (COS-7) that produced the highest level of antigen expression performed best in Western blot analysis screens. In summary, intravenous delivery of antigen-expressing plasmid DNA vectors is an effective genetic immunization method for the induction of antigen-specific antibodies in small and large research animals.